Law and Literature: a theoretical perspective - Zolezzi Ibárcena, Lorenzo (2013)
While most of the Law and Literature books and articles stress from the beginning the distinction between Law in Literature and Law as Literature, my approach is from the standpoint of Law teaching. A course on Law and Literature will help the students not only to write better, but it may convey the students facts that surround the work of the formal legal systemas the human condition or the legal culture, as well as a legal perspective thatis, so to speak, engraved in the human mind. The so-called didactic school is treated and criticized. The distinction between Law in Literature and Law as Literature cuts across the whole work.